FAKTOR YANG MEMPENGARUHI KONVERSI LAHAN PERTANIAN STUDI KASUS: KECAMATAN JATEN, KABUPATEN KARANGANYAR - Fadlli, Yuniar Irkham; Soedwiwahjono, Soedwiwahjono; Hardiana, Ana (ARSITEKTURA, 2016)
Surakarta City experienced population growth and rapid economic development, while land availability is limited so that the developments leading to suburban areas. Such as in Jaten that have a high-intensity agricultural land conversion caused by the high rate of population growth and the development of market mechanisms as a result of the economic development in Jaten. Jaten also has a high level of productivity of agricultural land. Therefore, needs to be studied further in Jaten why a lot of agricultural land conversion?The method of this research is deductive. The data analysis technique used is qualitative by using crosstab analysis to determine an influence factor the conversion of agricultural land to the phenomenon the conversion of agricultural land in the district Jaten and descriptive analysis of qualitative to determine the factor that affect the conversion of agricultural land in Jaten.Results of this study is factor that affect the conversion of agricultural land in Jaten include population growth caused by high birth rates, GDP District of Jaten where the sector processing industry is a sector basis, the price of land, farmers' preferences, availability of infrastructure and government policy.